Sliding mode methods for fault detection and fault tolerant control with application to aerospace systems - Edwards, Christopher; Alwi, Halim; Tan, Chee Pin (Zielona Góra: Uniwersytet Zielonogórski)
Sliding mode methods have been historically studied because of their strong robustness properties with regard to a certain class of uncertainty, achieved by employing nonlinear control/injection signals to force the system trajectories to attain in finite time a motion along a surface in the state-space. This paper will consider how these ideas can be exploited for fault detection (specifically fault signal estimation) and subsequently fault tolerant control.
Keywords: sliding modes; fault detection; fault tolerant control; control allocation